Electrophysiological and Morphological Characterization of Chrna2 Cells in the Subiculum and CA1 of the Hippocampus: An Optogenetic Investigation - Nichol, Heather; Amilhon, Bénédicte; Manseau, Frédéric; Badrinarayanan, Saishree; Williams, Sylvain (Frontiers in Cellular Neuroscience, 2018)
The nicotinic acetylcholine receptor alpha2 subunit (Chrna2) is a specific marker for oriens lacunosum-moleculare (OLM) interneurons in the dorsal CA1 region of the hippocampus. It was recently shown using a Chrna2-cre mice line that OLM interneurons can modulate entorhinal (EC) and CA3 inputs and may therefore have an important role in gating, encoding and recall of memory. In this study, we have used a combination of electrophysiology and optogenetics using Chrna2-cre mice to determine the role of Chrna2 interneurons in the subiculum area, the main output region of the hippocampus. We aimed to assess the similarities between Chrna2 subiculum and CA1 neurons in terms of the expression of interneuron markers, their membrane properties and their inhibitory input to pyramidal neurons. We found that subiculum and CA1 dorsal Chrna2 cells similarly expressed the marker somatostatin (Som) and had comparable membrane and firing properties. The somas of Chrna2 cells in both regions were found in the deepest layer with axons projecting superficially. However, subiculum Chrna2 cells displayed more extensive projections with dendrites which occupied a significantly larger area than in CA1. The post-synaptic responses elicited by Chrna2 cells in pyramidal cells of both regions revealed comparable inhibitory responses elicited by GABAA receptors and, interestingly, GABAB receptor mediated components. This study provides the first in-depth characterization of Chrna2 cells in the subiculum, and suggests that subiculum and CA1 Chrna2 cells are generally similar and may play comparable roles in both sub-regions.